The 4th wave evolution of digital citizenship concept? Proposing digital citizenship concept for Malaysia context - Ahmad, Nur Atikah; Hassan, Aminuddin; Syed Abdullah, Sharifah Intan Sharina; Salim, Siti Suria (Macrothink Institute, 2021)
Online world demands new sets of characteristics to warrant the ability to cope with its constantly evolving challenges and risks. Digital citizenship, a concept introduced, focusing on new ways of learning and exploring in an online environment safely, securely, and appropriately. The evolution of digital citizenship could be seen along with the changes in technology used in education, and requires students to engage with technology longer hours than before. Thus, how can we approach the challenge of using technology actively and immersively, while maintaining sanity and wellness, and building resilience to potential online risk? Thus, this conceptual paper proposes a new concept of digital citizenship by bridging the notions of wellness and resilience from the psychology discipline into digital citizenship, for its feasibility in the Malaysian educational context. This paper argues the necessity and potential integration of the spiritual element that is lacking in the existing digital citizenship concept, which has proven its significance in enhancing wellness and resilience of adolescent in the literature. It is hoped this fourth wave of proposed digital citizenship concept would bring fruitful discussion and contribute to a better understanding of how one might better socialize online or participate with others in a positive and meaningful way. Thus, only then, digital resilience and digital wellness will be established and a better future online society will be formed.